2010
DOI: 10.4161/psb.5.11.13318
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of proteins ofOryza sativaL. in the model tobacco and tomato plants

Abstract: The cellular localization and molecular interactions are indicative of functions of a protein. The development of a simple and efficient method for subcellular localization of a protein is indispensable to elucidate gene function in plants. In this study, we assessed the feasibility of Agrobacterium-mediated transformation (agroinfiltration) of tobacco and tomato leaf tissue to follow intracellular targeting of proteins from rice fused to green fluorescent protein (GFP). For this, a simple in planta assay for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…However, living cell imaging to monitor gene expression is possible using fluorescent proteins without additional substrates and cofactors (Ehrhardt, 2003). Indeed, fluorescent proteins are usually employed as useful tools to visualize protein localization in living cells in land plants (Buschmann et al, 2010;Kokkirala et al, 2010;Meng et al, 2010;Pribat et al, 2010). We first examined the usability of fluorescent proteins as reporters in P. yezoensis cells, since the expression of fluorescent protein has not yet been demonstrated in red algal cells.…”
Section: Development Of Fluorescent Protein Reporter Systemmentioning
confidence: 99%
“…However, living cell imaging to monitor gene expression is possible using fluorescent proteins without additional substrates and cofactors (Ehrhardt, 2003). Indeed, fluorescent proteins are usually employed as useful tools to visualize protein localization in living cells in land plants (Buschmann et al, 2010;Kokkirala et al, 2010;Meng et al, 2010;Pribat et al, 2010). We first examined the usability of fluorescent proteins as reporters in P. yezoensis cells, since the expression of fluorescent protein has not yet been demonstrated in red algal cells.…”
Section: Development Of Fluorescent Protein Reporter Systemmentioning
confidence: 99%
“…In silico prediction of subcellular localization suggested that majority of OsTET proteins are targeted to plasma membrane, with two exceptions, of OsTET6 and OsTET7 genes that were predicted to reside in chloroplast, and endoplasmic reticulum, respectively. Transient expression of genes is a reliable, simple, and rapid approach for determining the subcellular localization of several plant proteins ( Kokkirala et al, 2010 ). We employed model plant system N. benthamiana (tobacco) leaves for agroinfiltration of several OsTET-YFP fusion constructs.…”
Section: Resultsmentioning
confidence: 99%
“…We transformed the plasmids into the Agrobacterium tumefaciens strain GV3101 by the heat shock method. Then, the Agrobacterium tumefaciens with plasmids was injected into the young leaves of 4-week-old tobacco plants in accordance with a previously described method [64]. After 48 h, we observed and photographed the lower epidermal cells of the leaves with a confocal laser scanning microscope (Leica, Germany).…”
Section: Subcellular Localization Of the Gsgis3 Proteinmentioning
confidence: 99%